2021
DOI: 10.1177/15347346211024566
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Origin of Positive Tissue Pressure During Negative-Pressure Wound Therapy

Abstract: This report provides a simplified insight into the previously unexplained physical mechanism of the origin of local positive tissue pressure during negative-pressure wound therapy (NPWT). A chain of 2 spring model could be used to show the biomechanical interaction between the NPWT dressing and the adjacent body tissues. It is important to assume that the application of NPWT dressing to the body surface creates a new closed compartmentalized volume. Air suction generates local positive pressure within the dres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…In this regard, I would like to congratulate Macionis for his eloquent explanation of this seemingly paradoxical finding in his letter titled, "Mechanism of Origin of Positive Tissue Pressure During Negative-pressure Wound Therapy." 4 Together with his schematics, which illustrate the physics at hand, he puts forward a very coherent explanation for the findings of the aforementioned studies, by comparing the foam and underlying tissues to 2 springs within a cylinder. Reduction of pressure from suction within the upper spring compartment (analogous to the foam) results in compression of the spring by the external atmospheric pressure.…”
Section: Dear Sirmentioning
confidence: 89%
“…In this regard, I would like to congratulate Macionis for his eloquent explanation of this seemingly paradoxical finding in his letter titled, "Mechanism of Origin of Positive Tissue Pressure During Negative-pressure Wound Therapy." 4 Together with his schematics, which illustrate the physics at hand, he puts forward a very coherent explanation for the findings of the aforementioned studies, by comparing the foam and underlying tissues to 2 springs within a cylinder. Reduction of pressure from suction within the upper spring compartment (analogous to the foam) results in compression of the spring by the external atmospheric pressure.…”
Section: Dear Sirmentioning
confidence: 89%
“…While rigid devices, such as suction cups, reduce tissue pressure and increase perfusion, 7 the same cannot be said for NPWT dressings, as they are non-rigid (collapsible). 8 A thesis on "The Biomechanics of Negative-pressure Wound Therapy" 2 demonstrated that NPWT increases tissue pressure 9,10 and reduces perfusion 5 (in contrast to the suction cup principle), and these findings have been supported by others. 8,[11][12][13] Another reason for the controversy about perfusion is the large body of historical evidence demonstrating that NPWT increases perfusion, with the most frequently cited paper being the seminal study of Morykwas et al 14 Morykwas and most other authors studying perfusion used laser Doppler to measure perfusion, which brings us to our third and last concern on Muller-Seubert's article.…”
mentioning
confidence: 92%
“…While rigid devices, such as suction cups, reduce tissue pressure and increase perfusion, 7 the same cannot be said for NPWT dressings, as they are non‐rigid (collapsible). 8 …”
mentioning
confidence: 99%
See 1 more Smart Citation